PENGARUH BIAYA CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - SETIAWATI, IIN (Jurnal Akuntansi AKUNESA, 2016)
Abstract   The purpose of this study is to research the corporate social responsibility cost on tax aggressiveness with profitability as a moderating variable. Based on the characteristics of the problem under study, the research is an empirical study. The data used is secondary data. The population is 129 agriculture companies, mining companies, and base and chemical industry companies listed in Indonesia Stock Exchange (BEI) with study period of 2011-2015, which was chosen by purposive sampling in order to take sample 5 companies that meet the criteria of the sample. The technique used for data analysis in simple linier regression and Moderated Regression Analysis (MRA) test. The results showed that the cost of corporate social responsibility positive effect on the tax aggressiveness. However profitability as a moderating variable can’t strengthen relations corporate social responsibility costs on tax aggressiveness. Keyword: corporate social responsibility cost, profitability, tax aggressiveness